2012
DOI: 10.2147/oajsm.s37035
|View full text |Cite
|
Sign up to set email alerts
|

Changes in single skinfold thickness in 100 km ultramarathoners

Abstract: BackgroundChanges in single skinfold thickness and body fat have been investigated in ultraswimmers and ultracyclists, but not in ultrarunners. The present study investigated the changes in single skinfold thickness during a 100 km ultramarathon.MethodsFirstly, we investigated associations between prerace preparation and prerace body composition and, secondly, changes in single skinfold thickness during a 100 km ultramarathon in 219 male ultramarathoners. Changes in fat mass and skeletal muscle were estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 46 publications
2
9
3
1
Order By: Relevance
“…However, the observed difference between the skinfold thickness before and after the race in this study was only observed in the triceps site. These results are consistent with those of Knechtle et al (2012) who found small decreases in individual skinfolds (from 0.0 to -2.8%) but an increase of 4.8% in the triceps skinfold. In addition, the significant decrease in the calf girth, higher than in the rest of girths could be associated with a large strain of running in this part of the lower limb (Knechtle et al 2012).…”
Section: R a F Tsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the observed difference between the skinfold thickness before and after the race in this study was only observed in the triceps site. These results are consistent with those of Knechtle et al (2012) who found small decreases in individual skinfolds (from 0.0 to -2.8%) but an increase of 4.8% in the triceps skinfold. In addition, the significant decrease in the calf girth, higher than in the rest of girths could be associated with a large strain of running in this part of the lower limb (Knechtle et al 2012).…”
Section: R a F Tsupporting
confidence: 92%
“…The loss in body mass following the event is consistent with data obtained in 100 km ultramarathoners (Knechtle et al 2012), ultra-endurance cyclists (Bischof et al 2013) and ultraendurance open water swimmers (Knechtle et al 2012). Bischof et al (2013) showed a larger decrease in individual skinfold thicknesses (from -6.4 to -14.9%) and in the sum of skinfolds (-10.7%) in cyclists.…”
Section: R a F Tsupporting
confidence: 87%
“…A further anthropometric characteristic related to endurance performance is the circumference of limbs of the upper arm, the thigh and the calf (15,17,29). …”
Section: Discussionmentioning
confidence: 99%
“…However, in ultra-endurance sports, some of the above-mentioned anthropometric and physiological characteristics can be of advantage, for example, a higher percentage of body fat serving as an energy store [29]. Furthermore, ultra-endurance sports are less dependent on anaerobic energy supply, which is preserved by the impact of testosterone.…”
Section: The Gender Gap Was Reduced In Longer Ultra-cycling Race Distmentioning
confidence: 99%